Landwirtschaft und Agrarpolitik in Deutschland und Frankreich auf der Suche nach neuen Wegen - Hermann Schlagheck (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– Seeking new ways in agriculture and agricultural policy in Germany and France. The concept of integrated rural development also represents a suitable approach for solving rural development problems in Europe. There are several reasons supporting the concept of rural development: changing framework conditions require new solutions and policies; rural areas need region-specific-development concepts; complex decision making requires cooperation between different actors and levels; sector-specific support remains part of region-specific development concepts; integrated rural development is time-consuming and requires intensive communication. A future-oriented sustainable policy for rural areas has to consider all functions of agriculture in a society, and this perspective can only be achieved with an integrated development approach.
Keywords: 330; Agrarpolitik; Ländliche Entwicklung; Deutschland; Frankreich